GAME EDUKASI MATEMATIKA “Tang Mane Bakoel Saprahan” DENGAN KONTEKS KEARIFAN LOKAL MELAYU KALIMANTAN BARAT - Riyanti Nurdiana; Siti Nur Asmah (STKIP Singkawang, 2022)
This study aims to activate students activities by playing while learning, reducing the use of gadgets by increasing physical activity and making it easier for students to understand the coordinate material system with the language and culture in their area. The research method used is the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results showed that the mathematics education game